Dual Infection of Pepper Yellow Leaf Curl Virus and Chilli Veinal Mottle Virus in Causing the Yellow leaf Curl Disease on Chili - Trisno, Jumsu; Jamsari, Jamsari; Hidayat, Sri Hendrastuti (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2021)
Yellow leaf curl disease is the primary disease in chili plants with up to 100% losses. Detection from the field showed a mixed infection between Geminivirus or Pepper Yellow Leaf Curl Virus (PYLCV) and several viruses, including Chilli Veinal Mottle Virus (ChiVMV) and Cucumber mosaic Virus (CMV). Therefore, this study aimed to determine the role of PYLCV and ChiVMV dual infection in influencing the development of chili yellow leaf curl disease. This study used a completely randomized design (CRD) with six treatments and ten replications. The treatments used were multiple Geminiviruses and ChiVMV infections simultaneously, before ChiVMV co-infection, after Geminivirus infection, single infection and whithout infection viruses. The results showed that the presence of ChiVMV infection before, after, and concurrently with Geminiviruses infection could increase the yellow leaf curl disease intensity and reduce plant height and wet weight growth. The mean scale value of ChiVMV infection before, after, and concurrently with Geminiviruses infection were 3.38, 3.90 and 3.58 compared to single Geminiviruses infection (scale of 3.20) and single ChiVMV (scale of 1.33). The interaction analysis of ChiVMV and geminiviruses infections based on the percentage reduction in plant growth height and wet weight showed additive interaction. ChiVMV co-infection further exacerbated the incidence of yellow leaf curl diseases in chilies.